Histological Pattern of Oral Carcinoma and its Association with Different addictive Risk Factors (Medical Forum Monthly, 2024)
Objective: Objective of this study was to find out association between histopathology of oral carcinomas and addictive risk factors.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at Dental OPD, Liaquat University Medical Hospital and department of Pathology LUMHS Jamshoro/ Hyderabad from 2015 to 2016.Materials and Methods: Total60 patients were included in the study having oral carcinomas. Careful clinical assessment following by complete medical history along with clinical examination was carried out. All the addictive cases were selected. All the information of various parameters like age, gender of patient, relevant clinical history, tobacco habit, other addictive associated risk factor, and microscopic histopathological findings of tissue specimen were carried out. All the addictive risk factor’s association was noted with types of oral carcinoma.Results: Out of these 60 patients, maximum number of patients i.e. 29 (48.33%) were from > 50 years of age group. Majority of patients 35(58.33%) were illiterate while only 6(10%) were graduate. Majority of patients 21(35%) had carcinoma in buccal mucosa. Majority of the cases 46.66% multiple addictive habits, while only tobacco chewing, betal nut/manpuri, gutka, naswar and tobacco smoking habits were found with percentage of 8.34%, 10%, 8.34%, 6.66% and 20% respectively. According to histopathological findings squamous cell carcinoma was the most common in 85% of the cases, following by verrucous carcinoma in 6.67%, Micro-invasive SCC was only in 1 patient and other non-squamous cell carcinomas were found in 6.67% of the cases.On the association between histological findings and addictive risk factors no significant difference was found between squamous cell carcinoma and addictive risk factors p value 0.112, while VC, MISCC and other non-squamous cell carcinoma were significantly associated with patients having multiple addictive habits p value 0.02.Conclusion: We concluded that multiple mix addictions of tobacco chewing and smoking, gutka, naswar andbetal nuts are significantly associated with oral carcinomaand potentially increases the chances of oral malignancy in certain pre malignant conditions.